TAXOPETIC : proposta de uma taxonomia para a classificação dos artefatos gerados pela metodologia PETIC - Fontes, Adriana de Melo (2016)
Advances in Information and Communication Technologies (ICT) can provide competitive advantages for organizations. The search for innovations by organizations demand better solutions for the constant technology and market advancements and the guarantee of quality and satisfaction to its customers. In this sense, organizations need that the Strategic Planning (PE) and ICT be integrated, coherent and with synergy to ensure the survival of organizations. The PETIC Methodology is a form of PE that safely help managers identify the maturity and consequent improvement of ICT processes required in company management. The growing number of case studies of PETIC in organizations has shown a difficulty to locate and classify PETIC Artifacts produced during these case studies. In this context, the use of classificatory structures (taxonomies) has been successfully applied to the classification and retrieval of information. This work proposes a taxonomy to support methodology PETIC called TAXOPETIC. Among the various technical approaches to build a taxonomy, we opted for the use of approaches Aganette et al. (2010) and Bayona-Oré et al. (2014). After the construction of TAXOPETIC, we performed a comparative study between these used approaches. In this paper, we present the reasons of choosing Bayonne-Oré et al approach. (2014). To test the TAXOPETIC structure, a software product called TAXOPETICWeb was built. Among the results, it was evident that the non-use of TAXOPETICWeb tool disables the centralized and classified access to Artifacts PETIC legacy. The TAXOPETICWeb enables the storage of all rated PETIC artifacts and, through the defined metadata tags, allows the most efficient location and categorizes the artifacts stored in PETIC TAXOPETICWeb.